Psychotherapeutic and neurobiological processes associated with ayahuasca: A proposed model and implications for therapeutic use - Perkins, Daniel; Ruffell, Simon G. D.; Day, Kimberley; Pinzon Rubiano, Diego; Sarris, Jerome (Frontiers in Neuroscience, 2023)
Ayahuasca is a psychoactive Amazonian plant brew. It is usually made from the Banisteriopsis caapi vine (Spruce ex Griseb. Morton, Malpighiaceae), which contains three primary harmala alkaloids, along with the leaves of Psychotria viridis (Ruiz et Pavon, Rubiaceae) in which the potent psychedelic dimethyltryptamine (DMT) is found. DMT-harmaloid concoctions have gained popularity in recent years, due to growing anecdotal and scientific reports of therapeutic benefits associated with their consumption. Ayahuasca is now ingested in a variety of different settings across the globe, from traditional ethnobotanical to so called “neo-shamanic” ceremonies. Furthermore, related preparations involving alternative sources of DMT and harmala alkaloids are becoming increasingly common as knowledge of ayahuasca continues to spread internationally. This paper reviews the existing literature and draws on original qualitative data from a large cross-sectional study of ayahuasca drinkers, to propose a model of psychotherapeutic processes associated with the consumption of ayahuasca. We assert that it is these processes, facilitated by a range of neurobiological effects, that lead to beneficial mental health and wellbeing outcomes. Our proposed model identifies five key psychotherapeutic processes or effects inherent to the ayahuasca experience; somatic effects; introspection and emotional processing; increased Self-connection; increased spiritual connection, and finally the gaining of insights and new perspectives. We note some important differences in these processes compared with other classic psychedelics as well as the implications of the model for the therapeutic use of ayahuasca. Improved understanding of the psychotherapeutic processes involved with the ayahuasca experience will better equip practitioners to work with this potentially transformative concoction and enable the optimisation of therapeutic treatment models for potential clinical use.